Fas Ligand localizes to intraluminal vesicles within NK cell cytolytic granules and is enriched at the immune synapse - Lee, Jeansun (Immun Inflamm Dis, 2018)
INTRODUCTION: T cell and NK cell cytotoxicity can be mediated via the perforin/granzyme system and Fas Ligand (FasL, CD178). FasL is synthesized as a type II transmembrane protein that binds its cognate receptor Fas (CD95). Membrane‐bound FasL is expressed on the plasma membrane of activated lymphocytes and is the main form of FasL with cytotoxic activity, but whether FasL is delivered to the immune synapse along with granzyme and perforin‐containing granules is unclear. METHODS: We stably expressed FasL‐fluorescent fusion proteins into human NK cells and examined the localization of FasL relative to other intracellular markers by confocal and immunoelectron microscopy, and examined the trafficking of FasL during formation of immune synapses with HLA‐deficient B cells. RESULTS: FasL co‐localized with CD63 more strongly than perforin or Lamp1+ in cytolytic granules. Electron microscopy revealed that FasL is enriched on intraluminal vesicles (ILVs) adjacent to the dense‐core within cytolytic granules. In NK cells forming immune synapses with HLA‐deficient B cells, a portion of FasL‐containing granules re‐localize toward the immune synapse, while a distinct pool of FasL remains at the distal pole of the cell. CONCLUSIONS: Localization of FasL to intra‐luminal vesicles within cytolytic granules facilitates FasL trafficking to immune synapses and cytotoxic function in NK cells.